The Implementation of a Return-to-Play Protocol with Standardized Physical Therapy Referrals in a Collegiate Football Program: PT’s Role in Return-to-Play, A Clinical Commentary - Andrew Teare-Ketter; Jeffrey Ebert; Hunter Todd (International Journal of Sports Physical Therapy)
Sport-related concussions (SRCs) are multi-faceted injuries requiring coordinated care for return-to-play (RTP). Although the number of concussions in collegiate football is increasing annually, there is poor standardization among RTP protocols. Recent evidence suggests there is an increased risk of lower extremity injury, neuropsychiatric consequences, and re-injury after SRC, and risk factors for a prolonged recovery from SRC have also been identified. Evidence demonstrates a faster RTP and improved outcomes with early physical therapy intervention; however, this is not yet common practice in the treatment of acute SRC.